2009
DOI: 10.1021/jp902384v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron on the Activation Energy of the Decomposition of LiBH4

Abstract: We studied the decomposition reaction kinetics of lithium borohydride (LiBH4) with and without boron as an additive under various hydrogen pressures. The decomposition of LiBH4+B was studied by means of differential scanning calorimetry and thermogravimetry. Boron addition improves the dehydrogenation process, resulting in a decomposition temperature of 150 °C. A novel model was applied to separate thermodynamic and kinetic effects and to evaluate the activation energy of decomposition. The model takes into ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 15 publications
4
38
1
Order By: Relevance
“…From these data, the orthorhombic-to-hexagonal tran-sition temperature may be calculated by linear extrapolation to 0.0001 GPa pressure as T trs ¼381.670.5 K, as shown in Figure A2 in Appendix: Supplementary data. A value of T trs ¼383 K was obtained for the polymorphous transformation temperature by Pendolino et al [37] using DSC. From a selection of collected data (see Table 2), an average selected value of T trs ¼38372 K has been considered for the assessment.…”
Section: Standard Enthalpy Of Formationmentioning
confidence: 99%
“…From these data, the orthorhombic-to-hexagonal tran-sition temperature may be calculated by linear extrapolation to 0.0001 GPa pressure as T trs ¼381.670.5 K, as shown in Figure A2 in Appendix: Supplementary data. A value of T trs ¼383 K was obtained for the polymorphous transformation temperature by Pendolino et al [37] using DSC. From a selection of collected data (see Table 2), an average selected value of T trs ¼38372 K has been considered for the assessment.…”
Section: Standard Enthalpy Of Formationmentioning
confidence: 99%
“…Destabilization of LiBH 4 was also achieved by the addition of different oxides with the following order of efficiency: Fe 2 O 3 > V 2 O 5 > Nb 2 O 5 > TiO 2 > SiO 2 [10]. More recently, Pendolino and coauthors demonstrated that the desorption temperature of LiBH 4 can be decreased from 500°C to 350°C by the addition of boron [12].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, in order to tailor the thermodynamics and the kinetics of LiBH 4 de-hydrogenation process, different approaches were proposed which can be classified in three categories: the addition of catalysts, the nanoconfinement into scaffolds and the destabilization of the tetrahydroborate by combination with a hydride phase. Doping with several additives including halides, oxides and pure metals effectively reduces the dehydriding temperature of LiBH 4 [8][9][10][11][12]. For example, Au et al verified that the halides TiF 3 , TiCl 3 and ZnCl 2 , when added to LiBH 4 , form unstable transition metal borohydride species which contribute to drastically reduce the thermal desorption temperature of the doped LiBH 4 from 300°C to less than 100°C [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 27 To force the reaction via Li 2 B 12 H 12 and overcome the kinetic barrier, the temperature has to be high enough, such as 873 K. At the same time, the direct decomposition has to be suppressed by applying an external pressure. A too high pressure on the other hand would stabilize the LiBH 4 and prevent the decomposition.…”
Section: Introductionmentioning
confidence: 99%